The Impact of Project-Based Learning on Deep Learning: Enhancing Meaningful, Mindful, and Joyful Learning in EFL Contexts - Tiara Ramadana; Abdul Halim; Ibrahim Ibrahim (Universitas Lambung Mangkurat, 2025)
This study examines how project-based learning (PBL) impacts deep learning by emphasizing meaningful, mindful, and enjoyable learning aspects in learning English ,as a foreign language (EFL). PBL involves students in real projects and encourages them to collaborate, participate and solve problems. This research shows that using PBL can improve students' learning skills in English as a foreign language (EFL). This research uses a thematic analysis method. The sample of this study was 30 students of grade 11 of MA PPKP RIibathul Khail Tenggarong, who had previously participated in English learning using the project-based learning (PBL) method. The instruments used in this research include observation sheets, questionnaires, pre-test and post-test. The instruments will be tested for validity and reliability through expert validity assessments and Cronbach's Alpha reliability tests. Furthermore, the data will be analyzed using statistical analysis techniques.